2019
DOI: 10.3390/f10050392
|View full text |Cite
|
Sign up to set email alerts
|

Three Main Genes in the MAPK Cascade Involved in the Chinese Jujube-Phytoplasma Interaction

Abstract: Chinese jujube (Ziziphus jujuba Mill.) is an important economic forest species and multipurpose fruit tree in the family of Rhamnaceae. Phytoplasmas are significant prokaryotic pathogens, associated with more than 1000 plant diseases. Jujube witches' broom disease (JWB) is a typical phytoplasma disease, caused by 'Candidatus Phytoplasma ziziphi'. Mitogen-activated protein kinase (MAPK) cascades are highly universal signal transduction modules and play crucial roles in regulating innate immune responses in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…In this study, we demonstrate that several ZjMAPKKKs, such as in vitro. This result is consistent with the findings of our previous work in which we found that ZjMPK1 was the gene potentially related to phytoplasma infection in vitro [17] but was different from our later finding that ZjMPK2 was likely regulating along with ZjMEK2 in vivo [23]. The reason behind this phenomenon may be that many more environmental factors (e.g., light and temperature) affect the development of a phytoplasma infection in vivo.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In this study, we demonstrate that several ZjMAPKKKs, such as in vitro. This result is consistent with the findings of our previous work in which we found that ZjMPK1 was the gene potentially related to phytoplasma infection in vitro [17] but was different from our later finding that ZjMPK2 was likely regulating along with ZjMEK2 in vivo [23]. The reason behind this phenomenon may be that many more environmental factors (e.g., light and temperature) affect the development of a phytoplasma infection in vivo.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, ZjMPK2, ZjMKK2 and ZjMKK4 have been shown to be the main genes involved in the Chinese jujube-phytoplasma interaction. Additionally, using yeast two-hybrid analyses, it has been demonstrated that ZjMKK2 interacts with ZjMPK2 [17,23]. All these results demonstrate the important function of MAPK cascades in response to phytoplasma infection in Chinese jujube.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, ZjMPK2, ZjMKK2 and ZjMKK4 have been shown to be the main genes involved in Chinese jujubephytoplasma interaction. Also, using yeast two hybrid analyses, it has been demonstrated that ZjMKK2 interacts with ZjMPK2 [18,24]. All these results demonstrate the important function of MAPK cascades in response to phytoplasma infection in Chinese jujube.…”
Section: Introductionmentioning
confidence: 72%